The Contribution of The Old and New Order Governments to Mathla'ul Anwar - Bahri, Saepul; Wasehudin, Wasehudin; Syafuri, Syafuri (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to analyze the contribution of the Old Order and New Order governments to Mathla'ul Anwar. The research method used is a literature study involving analysis of relevant primary and secondary sources. The results showed that the Old Order government provided ample space for the development of Mathla'ul Anwar, by providing support for Islamic education and social religious activities. However, under the New Order government, Mathla'ul Anwar experienced obstacles due to stricter control over religious organizations and government efforts to direct religious activities in accordance with official ideology. Despite this, Mathla'ul Anwar has survived and adapted to the changing times, showing its resilience as one of the significant Islamic organizations in Indonesia. This research provides a deeper insight into the dynamics of the relationship between the government and religious organizations in Indonesia, as well as the contribution of Mathla'ul Anwar in the context of political and social change during the Old Order and New Order periods.